Moral Ecologies
XIII, 306 p. 16 illus., 11 illus. in color.
Keywords: This book offers the first systematic study of how elite conservation schemes and policies define once customary and vernacular forms of managing common resources as banditry—and how the ‘bandits’ fight back. Drawing inspiration from Karl Jacoby’s seminal Crimes against Nature, this book takes Jacoby’s moral ecology and extends the concept beyond the founding of American national parks. From eighteenth-century Europe, through settler colonialism in Africa, Australia and the Americas, to postcolonial Asia and Australia, Moral Ecologies takes a global stance and a deep temporal perspective, examining how the language and practices of conservation often dispossess Indigenous peoples and settlers, and how those groups resist in everyday ways. Drawing together archaeologists, anthropologists, geographers and historians, this is a methodologically diverse and conceptually innovative study that will appeal to anyone interested in the politics of conservation, protest and environmental history.